Involvement of the food industry in nutrition conferences in Latin America and the Caribbean. Issue 6 (29th April 2021) - Mialon, Mélissa; Jaramillo, Ángela; Caro, Patricia; Flores, Mauricio; González, Laura; Gutierrez-Gómez, Yareni; Lay, Lina; López-Arana, Sandra; López-Bautista, Fabiola; Mata, Claret; Moliterno, Paula; Palomares, Lita; et al.
Abstract: Objective: Identify and characterise the food industry's involvement in nutrition and dietetics national and regional events in Latin America and the Caribbean. Design: Between February and April 2020, we conducted desk-based searches for nutrition and dietetics events held in the region between January 2018 and December 2019. Online freely accessible, publicly available information was collected on the involvement of the food industry through: sponsorship of events; sponsorship of sessions; speakers from the food industry; scholarships, fellowship, grants, awards and other prizes and; exhibition space/booths. Setting: Nutrition and dietetics events in Latin America and the Caribbean. Results: Thirty-one events held in twenty countries of the region had information publicly available online at the period of data collection. There was a lack of transparency on the involvement of industry actors in these events. When information was publicly available, we found that a total of ninety-two food industry actors sponsored 88 % of these events. Conclusions: There is a mostly unreported, but likely extensive, involvement of food industry actors in nutrition and dietetics events in Latin America and the Caribbean.